A Bioinert Hydrogel Framework for Precision 3D Cell Cultures: Advancing Automated High‐Content and High‐Throughput Drug Screening - Hyunsu Jeon; Tiago Thomaz Migliati Zanon; James Carpenter; Aliciana Ilias; Yamil Colón; Yichun Wang (Small Science)
Enhanced drug testing efficiency has driven the prominence of high‐content and high‐throughput screening (HCHTS) in drug discovery and development. However, traditional HCHTS in well‐plates often lack complexity of in vivo conditions. 3D cell cultures, like cellular spheroids/organoids, offer a promising alternative by replicating in vivo conditions and improving the reliability of drug responses. Integrating spheroids/organoids into HCHTS requires strategies to ensure uniform formation, systemic function, and compatibility with analysis techniques. This study introduces an easy‐to‐fabricate, low‐cost, safe, and scalable approach to create a bioinert hydrogel‐based inverted colloidal crystal (BhiCC) framework for uniform and high‐yield spheroid cultivation. Highly uniform alginate microgels are fabricated and assembled into a colloidal crystal template with controllable contact area, creating engineered void spaces and interconnecting channels within agarose‐based BhiCC through the template degradation by alginate lyase and buffer. This results in a multi‐layered iCC domain, enabling the generation of in‐vitro 3D culture models with over 1000 spheroids per well in a 96‐well plate. The unique hexagonal‐close‐packed geometry of iCC structure enables HCHTS through conventional plate reader analysis and fluorescent microscopy assisted by house‐developed automated data processing algorithm. This advancement offers promising applications in tissue engineering, disease modeling, and drug development in biomedical research.